" The role of applying the international standards of the Supreme Audit Institutions in achieving administrative reform and improving performance " - عبد الله بشرى نجم; عبد الحسين سهير موفق (Journal of Economics and Administrative Sciences, 2018)
Abstract The aim of the research is to introduce the international standards of the Supreme audit Institutions, as well as the role of these standards in achieving administrative reform and improving the performance of the Supreme audit Institutions and the performance of the economic units under its control. In order to achieve the objectives of the research, a questionnaire was designed from two main axes that included a number of questions addressed to a number of officials and employees of the Supreme Audit Institutions and its affiliated bodies on the role of applying the international standards of the Supreme Audit Institutions in achieving administrative reform and improving performance. The study concluded that the international standards of the Supreme Audit Institutions provide detailed guidelines that provide a general framework for ensuring that the supervisors have the competence, integrity and independence in planning, implementing and reporting the results of their work. The international standards of the Supreme Audit Institutions issued by INTOSAI and supported by the Federal Audit Bureau at all levels, with the need to support communication with other international, regional and Arab professional organizations and benefit from the experiences of Other countries in the adoption or compatibility of such standards